2013
DOI: 10.3201/eid1905.121062
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Type ofClostridium difficilein Neonatal Pigs, Western Australia

Abstract: Clostridium difficile causes neonatal enteritis in piglets; strains of PCR ribotype 078 are most commonly identified. We investigated C. difficile prevalence in piglets in Australia and isolated a novel strain with a unique pathogenicity locus. In a mouse infection model, this strain produced more weight loss than did a ribotype 078 strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 15 publications
4
41
0
Order By: Relevance
“…It is worth noting that toxin A þ BÀ isolates of C. difficile have not been described in nature. Toxin AÀ toxin Bþ strains have been widely reported in human cases [138] but also in animals suffering from diarrhoea [139]. A previous study reported that toxin AÀ toxin Bþ strains caused the same spectrum of disease that is associated with toxin Aþ toxin Bþ strains, ranging from asymptomatic colonisation to fulminant colitis, with outbreaks in hospitals and other healthcare settings worldwide [135].…”
Section: Difficile Characteristics and Its Toxinsmentioning
confidence: 99%
“…It is worth noting that toxin A þ BÀ isolates of C. difficile have not been described in nature. Toxin AÀ toxin Bþ strains have been widely reported in human cases [138] but also in animals suffering from diarrhoea [139]. A previous study reported that toxin AÀ toxin Bþ strains caused the same spectrum of disease that is associated with toxin Aþ toxin Bþ strains, ranging from asymptomatic colonisation to fulminant colitis, with outbreaks in hospitals and other healthcare settings worldwide [135].…”
Section: Difficile Characteristics and Its Toxinsmentioning
confidence: 99%
“…Up until recently, all known A Ϫ B ϩ toxinotypes had at least a part of the tcdA gene present and the entire or deleted version of tcdC (7). An Australian group described the first A Ϫ B ϩ variants (toxinotypes XXX and XXXI) lacking the complete tcdA gene and two accessory genes (tcdE and tcdC); however, each of these were binary toxin positive (A Ϫ B ϩ CDT ϩ ) (13,14). In addition to lacking tcdA and tcdC, toxinotype XXXII also has no binary toxin CDT genes (A Ϫ B ϩ CDT Ϫ ).…”
mentioning
confidence: 99%
“…This was supported by Couturier et al, who reported detection of the tcdA target sequence in A Ϫ B ϩ strains belonging to toxinotypes VIII and X using the illumigene C. difficile assay (13), and in the present study for RT017 (toxinotype VIII) strains which have a truncated tcdA gene retaining only the A1 fragment of the gene (4). Other A Ϫ B ϩ ribotypes tested (RT237, RT280, and RT281) that were known to contain a truncated tcdA region (14,15) were not detected by the illumigene C. difficile assay. Therefore, in addition to PaLoc-negative C. difficile, the target region of the illumigene C. difficile assay is not conserved in the PaLocs of RT033, RT237, RT280, and RT281 strains.…”
mentioning
confidence: 97%
“…As a common ribotype in veal calves and piglets in some parts of the world, the presence of RT033 isolates should be a concern for the veterinary industry (6,16). While the role of C. difficile in idiopathic diarrhea in calves is still unclear, C. difficile is the most frequent cause of piglet neonatal diarrhea in the United States (15). The RT033 strain has also been isolated from symptomatic human patients, suggesting possible zoonotic transmission (12).…”
mentioning
confidence: 99%